On the intrinsic value of consciousness - ELKATİP HATİPOĞLU, SİNEM (My University, 2023)
Is there value in the instantiation of phenomenal consciousness? While consciousness seems obviously valuable and life without consciousness does not seem to have much meaning to it, further investigation proves otherwise. Some have argued that consciousness may not be as significant and valuable as it may seem. Lee (2019) e.g. endorses the neutral view and argues that consciousness is neither intrinsically valuable nor disvaluable. In this paper, first I critically examine Lee’s (2019) argument for the neutral view. Then I suggest that in order to critically examine the question of whether consciousness is intrinsically valuable without confusing this question with the question of whether it is instrumentally valuable, value of consciousness needs to be considered as the value present in having a viewpoint. I then develop a way of understanding what having a viewpoint is. Lastly, I suggest that if consciousness or having a viewpoint has intrinsic value, it is of an epistemic kind.

Fenomenal bilince sahip olmanın bir değeri var mıdır? Bir taraftan bilincin önemi bariz ve bilinçsiz bir hayat anlamsız görünse de bazı düşünürler bilince atfedilen değeri eleştirmiştir. Örneğin Lee (2019) nötr görüşü kabul etmiş ve bilincin özünde ne değerli ne de değersiz olduğunu savunmuştur. Bu çalışmada önce Lee’nin (2019) nötr görüş için sunduğu sebepleri inceliyorum. Sonrasında bilincin özünde değeri olup olmadığı sorusunu bilincin araçsal değeri olup olmadığı sorusuyla karıştırmamak için bilincin özünde değerini, bakış açısına sahip olmanın değeri olarak düşünmeyi öneriyorum. Bu çerçevede bakış açısına sahip olmanın ne anlama geldiğini ele alıyor ve eğer bilincin ya da bakış açısına sahip olmanın özünde bir değeri varsa, bu değerin epistemolojik bir değer olduğunu öneriyorum.
Bilincin özünde değeri üzerine
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); value of consciousness; phenomenal consciousness; intrinsic value; instrumental value; epistemic value; neutral view; bilincin değeri; fenomenal bilinç; özünde değer; araçsal değer; epistemolojik değer; nötr görüş